Qualitative study about the ways teachers react to feedback from resident evaluations - van Roermund, Thea (BioMed Central, 2013)
BACKGROUND: Currently, one of the main interventions that are widely expected to contribute to teachers’ professional development is confronting teachers with feedback from resident evaluations of their teaching performance. Receiving feedback, however, is a double edged sword. Teachers see themselves confronted with information about themselves and are, at the same time, expected to be role models in the way they respond to feedback. Knowledge about the teachers’ responses could be not only of benefit for their professional development, but also for supporting their role modeling. Therefore, research about professional development should include the way teachers respond to feedback. METHOD: We designed a qualitative study with semi-structured individual conversations about feedback reports, gained from resident evaluations. Two researchers carried out a systematic analysis using qualitative research software. The analysis focused on what happened in the conversations and structured the data in three main themes: conversation process, acceptance and coping strategies. RESULTS: The result section describes the conversation patterns and atmosphere. Teachers accepted their results calmly, stating that, although they recognised some points of interest, they could not meet with every standard. Most used coping strategies were explaining the results from their personal beliefs about good teaching and attributing poor results to external factors and good results to themselves. However, some teachers admitted that they had poor results because of the fact that they were not “sharp enough” in their resident group, implying that they did not do their best. CONCLUSIONS: Our study not only confirms that the effects of feedback depend first and foremost on the recipient but also enlightens the meaning and role of acceptance and being a role model. We think that the results justify the conclusion that teachers who are responsible for the day release programmes in the three departments tend to respond to the evaluation results just like human beings do and, at the time of the conversation, are initially not aware of the fact that they are role models in the way they respond to feedback.